Measuring and evaluating safety management system effectiveness using Data Envelopment Analysis. (April 2018) - Stolzer, Alan J.; Friend, Mark A.; Truong, Dothang; Tuccio, William A.; Aguiar, Marisa
Highlights: A sound, valid means of SMS effectiveness measurement and evaluation has not been previously available. The purpose of this research was to develop a model for measuring and testing SMS effectiveness. An instrument was developed and made available to the aviation community. The instrument was found to be reliable with high convergent validity. The instrument is useful in identifying ineffective organizations and changes needed for improvement. Abstract: In January 2015, the FAA released a congressionally mandated, final rule on Safety Management Systems (SMS) for Part 121 air carriers. Since organizations must implement SMS, often at considerable expense, a sound, valid means of measuring SMS effectiveness must be established. The purpose of this research was to develop a model to measure and test SMS effectiveness. It was constructed through a systematic series of steps, ensuring accomplishment of research objectives. While preliminary, this research demonstrates that Data Envelopment Analysis (DEA) models can be produced to help organizations measure the effectiveness of their SMS and determine how to improve SMS-related performance.